1983
DOI: 10.1093/nar/11.18.6409
|View full text |Cite
|
Sign up to set email alerts
|

Nonviral heterogeneous sequences are present at the 5′ ends of one species of snowshoe hare bunyavirus S complementary RNA

Abstract: Analyses of the 5' ends of snowshoe hare bunyavirus plus sense S RNA species (including mRNA) recovered from infected cells have revealed two types of termini. These include ends that are essentially exact copies of the 3' end of the viral S RNA and others that are similar, but additionally have 13-14 nucleotide extensions that are heterogeneous in sequence. The former probably represent replicative plus sense RNA species, the latter mRNA species that have host cell derived primer sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
70
1
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 26 publications
5
70
1
1
Order By: Relevance
“…Some clones lacked either one, two or three of the predicted 5Ј-most nucleotides complementary (i.e., ACA) to the template genomic RNA (12,14). Furthermore, the mRNAs of the Bunyaviridae members typically lack one or three of the 5Ј viral nucleotides (18,27,29,39). Our analyses showed that 17, 1, and 20 of the clones obtained from the ␣, ␤, and ␥ BSMV͞MStV chimeric RNAs, respectively, also lacked either one or three of the first 5Ј nucleotides of the MStV RNA 4 sequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some clones lacked either one, two or three of the predicted 5Ј-most nucleotides complementary (i.e., ACA) to the template genomic RNA (12,14). Furthermore, the mRNAs of the Bunyaviridae members typically lack one or three of the 5Ј viral nucleotides (18,27,29,39). Our analyses showed that 17, 1, and 20 of the clones obtained from the ␣, ␤, and ␥ BSMV͞MStV chimeric RNAs, respectively, also lacked either one or three of the first 5Ј nucleotides of the MStV RNA 4 sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Members of both the Tenuivirus and Phlebovirus genera have a number of similarities including: multipartite genomes composed of both negative and ambisense segments; the genomic RNAs for viruses in each of these genera have eight identical nucleotides (5Ј-ACACAAAG) at the 5Ј termini of each genome segment while the 3Ј termini are conserved and complementary to the 5Ј termini; the genomes have similar arrangements of protein coding regions; and some of the encoded proteins for different viruses show significant similarity (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Transcription of the genomic RNAs yields mRNAs with capped 5Ј termini (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and between the cap and the viral RNA sequence are short stretches of nucleotides that are not of virus origin (12,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These viruses require host cell mRNA 5Ј caps plus adjacent oligonucleotides to prime their transcription. 15,16 The restriction in host cell biosynthetic activities that occurs during diapause could indirectly result in a reduction of viral replication due to a limiting supply of mRNA caps or other macromolecules needed for replication. 17 The reduction in host cell transcription during diapause could concomitantly reduce viral replication, thereby moderating deleterious effects to the embryo by preventing the depletion of host cell macromolecules and enhancing virus overwintering.…”
mentioning
confidence: 99%
“…[46][47][48][49][50] There is evidence for functional interactions between the 5′ and 3′ end of the negative sense viral genomic RNA segments and for the direct interaction between these and the viral nucleocapsid, N, and the RNA-dependent-RNA polymerase, L. 5,45 Transcription occurs in the cytoplasm and involves priming of viral transcripts using short, capped oligonucleotides derived from cellular mRNAs. [51][52][53][54][55] To enable this cap-snatching mechanism, which is analogous to that employed in the nucleus by Influenza A virus, the bunyavirus L proteins have cap-dependent endonuclease activity. 53,56 Although there is no direct evidence for this endonuclease activity for the Schmallenberg virus L, the protein does contain the conserved motifs associated with this activity in other bunyaviruses (Figure 2).…”
Section: Molecular Biologymentioning
confidence: 99%